Cultural aspects of English-Arabic Translation - Alkaabi, .Raheem Challub Seber Alkaabi (lark, 2020)
The criticalness of cultural issues served as the premise to examine the cultural issues in English-Arabic translation under Newmark's theory. Using a legitimate and fitting method in overseeing CSIs is one of the crucial stresses of every mediator. To this end, the present examination endeavored to show how cultural issues in English-Arabic translations are tended to cause problems in translation. In Newmark's (1988) theory there are 17 methodologies for translation of culture-explicit issues and one of them is a componential examination which is characterized by Newmark (1988) which was adopted in the present study. The results of the study revealed that the distinctions in terms of religious terms among Arabic and English translations of the participants were the most significant cultural issues in English-Arabic translation. The observed cultural issues in English-Arabic Translation were religion-text- related terms which were translated under the influence of religious culture of the Arab participants. The main implication of the study is the significant impact of religion-based cultural issues in English-Arabic translation.
Keywords: المصطلحات الرئيسية: القضايا الثقافية ؛ الترجمة الإنجليزية-العربية ؛ نظرية نيومارك